A Versatile Approach Towards the Fast Fabrication of Highly‐Permeable Polymer Mesoporous Membranes. Issue 12 (3rd August 2016) - Liu, Rongrong; Zhang, Qiugen; Lin, Zhen; Lv, Ruixue; Gao, Runsheng; Soyekwo, Faizal; Zhu, Aimei; Liu, Qinglin
Abstract: Polymer mesoporous materials have attracted increasing concerns in various fields especially in membrane separation process. Here we report a versatile approach to fabricate novel highly‐permeable polymer mesoporous membrane for size‐exclusion separation. This approach employs copper hydroxide nanowire thin films as the soluble templates to form a polymer mesoporous separation layer. The membrane formation mechanism is revealed by varying the polymer concentration, the thickness of template films and the size of nanowires. The resultant membranes have a three‐layer sandwich structure, allow fast permeation of water, and exhibit excellent size‐exclusion separation performances. Typically, the 1.39 µm‐thick membrane has a high water flux of 1.17 10 3 L m −2 h −1 bar −1 and rejections of 94.1 % for ferritin molecules. The developed approach have a great potential in the fabrication of polymer mesoporous materials, and produce the membranes have a wide range of applications including in environmental fields. Abstract : Novel highly‐permeable polymer mesoporous membranes are fabricated by a versatile approach that employ a soluble template layer of copper hydroxide nanowires to form a polymer mesoporous layer. The resultant membranes have a three‐layer sandwich structure, allow fast permeation of water, and exhibit excellent size‐exclusion separation performances. The newly mesoporous membranes have a wide range of applications including in life science and environmental fields.